1991
DOI: 10.1073/pnas.88.19.8357
|View full text |Cite
|
Sign up to set email alerts
|

A method for production of antibodies to human T-cell receptor beta-chain variable regions.

Abstract: Mouse T-cell hybridomas bearing human Vp elements were produced by transfection of human/mouse hybrid T-cell receptor 18-chain genes into a mouse T-cell hybridoma lacking an endogenous #-chain gene. These hybridomas were entirely mouse in origin except for the human Vp region. These cells were used to immunize mice against human V13 elements. Mouse monoclonal antibodies have thus been generated against human Vp13.1 and -13.2. We expect that the method outlined in this paper will be useful in the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…We simultaneously assessed activation of TCRBV8 T-cell hybridomas as a specificity control. Hybridoma assays were performed as described previously (52,53) by using the TCRBV13 T-cell hybridoma, hV␤13.1-1 (11,12) and the TCRBV8 T-cell hybrid YL␤8#24 (53). Figure 1A depicts the results of a representative hybridoma assay with two lymphoblastoid cell lines (LCL), Mg68 and 253.30, that were derived by transformation with EBV deletion mutants lacking the majority of the lytic genes.…”
mentioning
confidence: 99%
“…We simultaneously assessed activation of TCRBV8 T-cell hybridomas as a specificity control. Hybridoma assays were performed as described previously (52,53) by using the TCRBV13 T-cell hybridoma, hV␤13.1-1 (11,12) and the TCRBV8 T-cell hybrid YL␤8#24 (53). Figure 1A depicts the results of a representative hybridoma assay with two lymphoblastoid cell lines (LCL), Mg68 and 253.30, that were derived by transformation with EBV deletion mutants lacking the majority of the lytic genes.…”
mentioning
confidence: 99%
“…V␤ ϩ expansions in the colonic lamina propria were defined in reference to the percentage of CD4 ϩ or CD8 ϩ T cells staining positive for the same V␤ in the same subject's peripheral blood. This corrects for bias introduced by the influence of MHC and TCR genes on the level of expression of different V␤s in different individuals (27,31,33,35,36,40). In individuals where a particular CD4 ϩ of CD8 ϩ V␤ expansion was present in the peripheral blood, expansions in the same V␤ ϩ in the LP could not be defined by reference to the level of expression of that V␤ in the individual's peripheral blood.…”
Section: Variation In Tcr Expression In the Normal Colonmentioning
confidence: 96%
“…Studies of T-cell clones that recognize the HLA-A2-restricted influenza A matrix peptide-(58-66) (16) and of clones that recognize the HLA-B27-restricted influenza A nucleoprotein peptide-(383-391) (15) concluded that use of TCR Vp, NDNs, V0, and Ja Recently mouse T-cell hybridomas transfected with human V,3 elements have been used as a source of immunogen (9,11,14). Although these methods overcome many of the probGap-A3 lems, B-cell hybridomas derived with this protocol may show a low frequency of reactivity with the human Vp element.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) to the V chains of the TCR have been extremely difficult to generate, despite the availability of T-cell clones for >10 yr. The existing panel of mAbs recognizes only 20-25% of the Vp gene segment products and only three of the Va products (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Studies of the T-cell repertoire have suggested a conservation of TCR Va and Vp gene use in major histocompatibility complex-restricted antigen recognition (15,16) and also that limited TCR Va and V gene use may occur in some autoimmune diseases (17)(18)(19).…”
mentioning
confidence: 99%